(untitled) (Research, Society and Development, 2021)
Nursing has become an increasingly favorable sector for entrepreneurship, with the extension of the professional nursing service beyond the walls of the hospital environment. Entrepreneurship has been a way of achieving a promising new economic niche for this professional. This work aims to review the content produced about undertaking nursing, as well as assisting future research in the area. This is a narrative review, with a qualitative approach, where searches were made in several health journals, national and international, published in the period between 2011 and 2021. The result of the work shows that nursing is a dynamic profession, which requires resilience, nurse’s creativity and courage. Entrepreneurship in nursing is not the future of the profession, it is the present. Fortunately, the dynamics of the profession already enable nursing professionals to innovate, and as seen so far, innovating is one of the main elements of entrepreneurship. What is sought is a better and more complete academic training on the art of entrepreneurship while still in college. Understanding the risks and benefits of this action, before completing graduation, can define the professional profile of the graduates of the course.